Comparing estimated and self-reported mark-ups for formal and informal firms in an emerging market context - John Rand (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Using a 10-year panel survey covering Vietnamese manufacturing firms, we consistently obtain firm-specific mark-up estimates and relate these to firm-level formality. The average firm-specific mark-up using a trans-log revenue production function specification is estimated to be 1,445, with substantial underlying variation across firm size, location, sector, and ownership form. Zooming in on firm-level registration, we find a formality premium of 16 per cent, even when controlling for selection into formality. Moreover, a firm size threshold exists, confirming that smaller informal firms are less likely to reap eventual benefits of formalization. Finally, we find remarkable similarity between average self-reported and estimated mark-ups, but dynamic aspects of the two estimates along key firm dimensions differ substantially.
Keywords: D22; L25; O14; O53; 330; firm productivity and mark-ups; formality; Viet Nam